2016
DOI: 10.1111/dme.13272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on acute outcomes of percutaneous coronary intervention in chronic total occlusions: insights from a US multicentre registry

Abstract: Aim To examine the impact of diabetes mellitus on procedural outcomes of patients who underwent percutaneous coronary intervention for chronic total occlusion. Methods We assessed the impact of diabetes mellitus on the outcomes of percutaneous coronary intervention for chronic total occlusion among 1308 people who underwent such procedures at 11 US centres between 2012 and 2015. Results The participants' mean ± SD age was 66±10 years, 84% of the participants were men and 44.6% had diabetes. As compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…A notable finding of the present study was that the clinical outcomes did not differ significantly between participants with DM and those without DM. Our observations are consistent with those of 2 previous studies (32,39), which implies that patients with CTO and DM can achieve the same benefit from PCI as those without DM. Nevertheless, prospective, randomized studies are needed to directly compare the clinical benefits of PCI for CTO between patients with DM and those without.…”
Section: Analysis Of Factors Associated With Clinical Outcomessupporting
confidence: 93%
“…A notable finding of the present study was that the clinical outcomes did not differ significantly between participants with DM and those without DM. Our observations are consistent with those of 2 previous studies (32,39), which implies that patients with CTO and DM can achieve the same benefit from PCI as those without DM. Nevertheless, prospective, randomized studies are needed to directly compare the clinical benefits of PCI for CTO between patients with DM and those without.…”
Section: Analysis Of Factors Associated With Clinical Outcomessupporting
confidence: 93%
“…Finally, only 7 studies (1 randomized trial [ 7 ] and 6 observational studies) [ 8 13 ] were included in this analysis as shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, approximately 40% of the patients undergoing CTO-PCI also had DM [ 10 , 29 ]. Although CTO lesions are more complex in DM patients, 2 recent large CTO studies, in which contemporary dedicated equipment and skills, including hybrid algorithms, have been applied, reported that procedural success and the prevalence of periprocedural complications were acceptable and comparable in patients with versus without DM [ 12 , 30 ]. However, the long-term prognosis of CTO revascularization with PCI in DM patients remains controversial, and few RCTs have been designed to assess it specifically.…”
Section: Discussionmentioning
confidence: 99%